Employee Performance and The Effects of Work Discipline and Individual Ability, With Organizational Supervision as a Moderator - Umar Semarang; Abdul Rahman Jannang; Marwan Man Soleman; Muhammad Syafi'i A. Basalamah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to examine the influence of work discipline and individual ability on employee performance with organizational supervision as a moderator at Class II Ternate Harbor and Port Authority. The number of samples used in this study was 42 respondents with moderated regression analysis as an analytical technique. Based on the analysis conducted, the results of the study indicate that work discipline and individual abilities have a positive and significant influence on employee performance. In addition, the results also showed that organizational supervision is only able to moderate the relationship between individual abilities and employee performance, but not on the relationship between work discipline and employee performance. The findings in this study provide guidelines that can be considered by policy makers in an effort to improve employee performance by considering key factors such as work discipline, individual abilities, and organizational supervision.